Treasury Single Account (TSA) and Cost of Governance: Survey of MDAs in Anambra State - Nnamdi Lawrence Okeke; George Ezeala; Nonso John Okoye; Chinedu Francis Egbunike (Goodwood Publishing, 2023)
Purpose: This study employed a descriptive research design using a cross-sectional methodology, with surveys and field investigations to examine the relationships between study variables. Research Methodology: This study used a descriptive survey design, with primary data collected through structured questionnaires from 100 purposely selected respondents across ten Federal Ministries Departments & Agencies (MDA) in Anambra State. Results: The results show that e-accounting and Treasury Single Account (TSA) have a substantial impact on national spending by curbing leakages, but with little effect on federally generated revenue. Thus, e-accounting and TSA significantly impact the cost of governance. Conclusions: This study concludes that TSA and e-accounting systems significantly reduce financial mismanagement, accelerate public-sector transactions, and require stronger infrastructure, human resource training, and guidance from countries with successful TSA implementation. Limitations: The study relied only on questionnaire responses, which is the perception of public-sector employees in MDAs. Contributions: This study contributes to governance and policy research by identifying the benefits of TSA in reducing the overall cost of governance. Novelty: This study supports stakeholder theory and the public finance management perspective by showing that integrated government accounts improve financial tracking, monitoring, and overall fiscal visibility.